Polymorphisms in ENAM, AMBN, and KLK4 predispose Egyptian adults to dental caries: A cross-sectional study - Hassan Mossad Hassan Negm; Amina Fouad Farag; Rania Rashad Omar Omar Taha (Elsevier, 2024)
Objective: This study investigates the distributional discrepancies of four single-nucleotide polymorphic loci as correlatives and causatives of dental caries susceptibility among Egyptians. Method: We conducted a cross-sectional study through the genotyping of enamelin (ENAM rs3796703), ameloblastin (AMBN rs4694075), tuftelin 1 (TUFT1 rs78802584), and kallikrein 4 (KLK4 rs2242670) in 132 adults (males = 74, females = 58) and 72 controls (males = 40, females = 32) referred from various Egyptian hospitals. For each participant, the number of decayed, missing, and filled teeth was charted, and the presence of biofilm/gingivitis/fluorosis was assessed. Bitewing radiographs were taken to detect interproximal caries. In addition, statistical analysis was conducted using Chi-square test, odds ratios, and corresponding P-values. Results: The alleles and genotypes of ENAM rs3796703, AMBN rs4694075, and KLK4 rs2242670 correlated strongly with dental caries susceptibility. However, TUFT1 rs78802584 did not exhibit such associations. Conclusion: These findings suggest the potential role of ENAM, AMBN, and KLK4 as determinants of dental caries susceptibility among Egyptian adults. The role of ENAM, AMBN, and KLK4 genetic variants is determinant in influencing susceptibility to dental caries in the Egyptian population, providing valuable insights into the genetic aspects of oral health. However, the lack of associations of caries susceptibility with TUFT1 rs78802584 contradicts its cariogenic role in many ethnicities.